2013
DOI: 10.1161/circulationaha.112.000999
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Systolic Function in Organic Mitral Regurgitation

Abstract: Background— To assess the prevalence, determinants, and prognosis value of right ventricular (RV) ejection fraction (EF) impairment in organic mitral regurgitation. Methods and Results— Two hundred eight patients (62±12 years, 138 males) with chronic organic mitral regurgitation referred to surgery underwent an echocardiography and biventricular radionuclide angiography with regional function assessment. Mean RV EF was 40.4±10.2%, ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
123
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 56 publications
12
123
1
2
Order By: Relevance
“…As suggested by Le Tourneau et al (4) and as confirmed by our findings, there appears to be a relationship between elevated PASP and RV dysfunction, even though PASP may not be the main determinant of RV performance following mitral valve repair, due to the potential for reversibility.…”
Section: Commentsupporting
confidence: 89%
See 2 more Smart Citations
“…As suggested by Le Tourneau et al (4) and as confirmed by our findings, there appears to be a relationship between elevated PASP and RV dysfunction, even though PASP may not be the main determinant of RV performance following mitral valve repair, due to the potential for reversibility.…”
Section: Commentsupporting
confidence: 89%
“…This is supported by the findings of Le Tourneau et al (4) who have shown that biventricular impairment is a powerful predictor of both cardiovascular and overall survival. In addition, RV dysfunction has been recognized as a predictor for survival in patients with ischemic or dilated cardiomyopathy after mitral valve annuloplasty (25).…”
Section: Commentsupporting
confidence: 69%
See 1 more Smart Citation
“…In humans, right heart assessment has been shown to have a clinically relevant impact on predicting clinical status and outcome in a variety of cardiovascular diseases, including diseases conventionally viewed as left heart‐specific, such as mitral valve disease and HCM 12, 23, 24, 25, 26. Recently, RV function has also been shown to have prognostic value in dogs with arrhythmogenic RV cardiomyopathy and myxomatous mitral valve disease 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…The right contractile property is important because right ventricular remodeling may play an important role in clinical outcome of patients undergoing mitral valve surgery [17,18].…”
Section: Discussionmentioning
confidence: 99%